2015
DOI: 10.1152/ajprenal.00383.2014
|View full text |Cite
|
Sign up to set email alerts
|

Urinary proteins induce lysosomal membrane permeabilization and lysosomal dysfunction in renal tubular epithelial cells

Abstract: Lysosomal membrane permeabilization (LMP) has been shown to cause the release of cathepsins and other hydrolases from the lysosomal lumen to the cytosol and initiate a cell death pathway. Whether proteinuria triggers LMP in renal tubular epithelial cells (TECs) to accelerate the progression of renal tubulointerstitial injury remains unclear. In the present study, we evaluated TEC injury as well as changes in lysosomal number, volume, activity, and membrane integrity after urinary protein overload in vivo and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 29 publications
2
69
0
1
Order By: Relevance
“…Autophagy is a degradative process whereby cytoplasmic content is engulfed by lysosomes and destroyed [31]. It is well known that microtubule-associated protein 1 light chain 3 (LC3)-II and p62 are key markers used to monitor autophagic flux [26,32]. An increase in LC3-II indicates a buildup of autophagic vacuoles, reflecting either increased formation or decreased clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a degradative process whereby cytoplasmic content is engulfed by lysosomes and destroyed [31]. It is well known that microtubule-associated protein 1 light chain 3 (LC3)-II and p62 are key markers used to monitor autophagic flux [26,32]. An increase in LC3-II indicates a buildup of autophagic vacuoles, reflecting either increased formation or decreased clearance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that excessive protein in urine is not merely a marker of the kidney injury but has intrinsic cell toxicity that contributes to tubular injury and fibrosis (28). The protein droplets seen in the cytoplasm of proximal tubular cells are associated with an acceleration of tubulointerstitial damage via the proinflammatory response (13,27) and oxidative stress (15,18) in proximal tubules, which, in turn, leads to the excretion of chemokines and cytokines, resulting in inflammation, transformation of interstitial fibroblasts, and fibrosis (6). Therefore, tubular epithelial cells play a central role in orchestrating the progression of proteinuria-induced renal injury and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that mitochondrial dysfunction and mitochondrial reactive oxygen species are also involved in albumin-induced inflammasomes, but whether lysosomal dysfunction is related with oxidative stress is not known. Another recent study suggested that oxidative stress was involved in the lysosomal dysfunction induced by urinary proteins (18).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (13), mitochondrial translocation (14), potassium efflux (15), and the cytosolic release of lysosomal cathepsins (16) were identified as possible intermediate cellular signals (17). Several recent reports further demonstrated that the overloading of urinary proteins caused albumin accumulation in lysosomes, lysosomal membrane permeabilization and decreased lysosomal degradation in TECs (18,19). However, whether lysomoal dysfunction affected inflammasome activation in proteinuria-induced renal injury is the subject of intensive research.…”
mentioning
confidence: 99%